Diversities In Motion: Multifunctionality of Maize Production in Different Family Farming Systems in South and Central Mexico - Boué, C.; Zepeda Villarreal, Ernesto Adair; Martínez García, Gloria; López Ridaura, Santiago; Barba-Escoto, Luis; Camacho Villa, Tania Carolina (Universidad Autonoma de Yucatan. Facultad de Medicina Veterinaria y Zootecnia, 2023)
Background: Maize agricultural policy in Mexico has focused on a monofunctional vision of maize as a basic commercial product, through a bimodal vision of production systems (commercial and subsistence). However, the evidence suggests that the challenge of thinking about the multifunctionality of this crop must be faced due to the complexity of its relationship within different strata of society, to more adequately reflect the diversity of systems based on maize, as well as their flexibility to respond to new challenges and opportunities, and to have better public policy designs. Objective: This work seeks to delve into the importance of the multifunctionality of maize within the context of different types of production units in Central and Southern Mexico, which represent families that make use of different production systems based on maize. This diversity is not a simple cultural curiosity, but rather reflects the complex use of maize cultivation as an economic and cultural mechanism that provides stability to Mexican families who depend on maize as their main crop. Methodology: To describe the multifunctionality of maize in Mexico, we adopted a qualitative approach through in-depth interviews with 51 maize producers from different types of production unit (PU) in the states of Oaxaca, Chiapas, Mexico, and Puebla. A study of production units (PU) typologies carried out with information from 16 states of the country was taken as a basis, where five types of PU were characterized according to their available resources, maize management, and their social characteristics. Results: It was found that: (1) there is a clearly distinguishable PU gradient (where, in addition to the existence of commercial and subsistence units, three others were identified, with direct implications for the design of public policy) that use maize with several purposes; (2) multifunctionality is associated with the diversity of uses and genetic materials that PUs have, and; (3) the variety of functions of maize changes according to the importance of maize in each type of unit and trough time. Implications: This work is positioned in favor of an expanded vision of the maize sector in Mexico instead of a dichotomous vision, where maize systems behave as a fluid continuum where the context of the PU’s affects their relationship with maize, and the way in which they use this crop to face social, climatic, and economic changes, as well as their preferences as consumers, traditions, and cultural identities. Conclusions: This complexity calls to thinking about a pluridiverse maize policy that understands the social complexity of this crop through the multifunctional support it offers to different types of UP’s based on maize systems, and how these differences require more sophisticated institutional approaches. Key words: multifunctionality of agriculture; maize; farm typologies; diversification of agricultural activities; diversity of maize-based systems.